2022
DOI: 10.2147/vhrm.s378292
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Predictive Ability of Arterial Stiffness Parameters Including Cardio-Ankle Vascular Index, Pulse Wave Velocity and Cardio-Ankle Vascular Index0

Abstract: Cardio-ankle vascular index (CAVI) was developed to reflect the stiffness of the arterial tree from the aortic origin to the ankle. This arterial stiffness parameter is useful for assessing the severity of cardiovascular disease (CVD) and its risk. However, compared to pulse wave velocity (PWV), the conventional gold standard of arterial stiffness parameter, there has been a concern regarding CAVI that there are fewer longitudinal studies for CVD. Furthermore, the accuracy of CAVI for atherosclerotic diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Considering the adverse effect of stress on arterial stiffness, which mediates the development of MACE, another direction in the treatment of such patients may be behavioral therapy. Currently, there are no studies examining the effect of stress-limiting therapy on improving vascular function, as already noted [27]. Accordingly, future research is needed to determine whether stress-reducing behavioral interventions can lead to reductions in cardiovascular events through improvements in CAVI.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the adverse effect of stress on arterial stiffness, which mediates the development of MACE, another direction in the treatment of such patients may be behavioral therapy. Currently, there are no studies examining the effect of stress-limiting therapy on improving vascular function, as already noted [27]. Accordingly, future research is needed to determine whether stress-reducing behavioral interventions can lead to reductions in cardiovascular events through improvements in CAVI.…”
Section: Discussionmentioning
confidence: 99%
“…Experts highlight the clinical value of CAVI as a predictor of hypertension, cardiovascular diseases, kidney injury progression, cognitive decline and dementia, and cardiovascular and total mortality [ 59 ]. Furthermore, there is data that CAVI may be superior in predicting all-cause mortality, major cardiovascular outcomes and renal function decline compared to PWV [ 60 ]. The study of the validity of atherosclerotic calcified lesions demonstrated that CAVI can be used to assess atherosclerotic changes at all stages of disease progression [ 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…19 Longitudinal studies have been reported that CAVI is a superior technique than pulse wave velocity (PWV) to determine the severity of coronary artery disease. 20 It has been stated that CAVI improves with the control of diseases which accelerate the atherosclerosis such as diabetes and hypertension. 19 Studies have found that a significant relationship between the severe periodontitis and increased CAVI values.…”
Section: Introductionmentioning
confidence: 99%
“…CAVI measurements increases with age and is high even in mild atherosclerotic disease 19 . Longitudinal studies have been reported that CAVI is a superior technique than pulse wave velocity (PWV) to determine the severity of coronary artery disease 20 . It has been stated that CAVI improves with the control of diseases which accelerate the atherosclerosis such as diabetes and hypertension 19 …”
Section: Introductionmentioning
confidence: 99%